Una sfida possibile: la teoria della nascita in altri ambiti linguistici - Sulla traduzione di Istinto di morte e conoscenza - Vari, Autori (Il sogno della farfalla, 2023)
This article gathers some linguistic reflections shared by many translators (English, French, German, Portuguese and Spanish) who worked on translating the volume Death instinct and knowledge. On one hand the article highlights the general difficulties encountered in the translation process, which aims at transmitting the meaning of a text from one culture into another; on the other the authors propose in-depth reflections on some linguistic issues. Given the absolute originality of the theoretical content written by Massimo Fagioli, this work has represented a relevant challenge for translators who worked effortlessly on terminological research to propose an innovative language. Regardless of its complexity, translators’ experience proved that the translation of the Human Birth Theory in any linguistic context is absolutely possible, furtherly demonstrating the universality of its content.